2020
DOI: 10.3389/fimmu.2020.590568
|View full text |Cite
|
Sign up to set email alerts
|

PD-1 Blockade Reverses Obesity-Mediated T Cell Priming Impairment

Abstract: Despite obesity reaching pandemic proportions, its impact on antigen-specific T cell responses is still unclear. We have recently demonstrated that obesity results in increased expression of PD-1 on T cells, and checkpoint blockade targeting PD-1/PD-L1 surprisingly resulted in greater clinical efficacy in cancer therapy. Adverse events associated with this therapy center around autoimmune reactions. In this study, we examined the impact of obesity on T cell priming and on autoimmune pathogenesis using the mous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…However, a sometimes-complicated notion is that obesity also leads to compensatory immunosuppressive mechanisms to avoid a constant, full-blown pro-inflammatory response, similar controlling any immune reaction, to maintain homeostasis. These mechanisms include reduced absolute numbers of activated CD8 + T cells, T cell suppression by PD-1 [241,242], T cell exhaustion [243], and dysfunctional NK cells [244]. Thus, obesity induces a complex and dynamic state of pro-inflammatory immune cell content and function with an influx of monocyte-derived "M1"-like macrophages, combined with reductions in immunomodulatory/ regulatory or dysfunctional immune cells such as regulatory T cells (Tregs), "M2"-like macrophages, or NK Cells, together with an induction of checkpoint ligands (discussed below) [245][246][247][248], and elevated immunosuppressive cells such as immature monocytes or myeloid-derived suppressive cells (MDSCs) [249][250][251][252][253].…”
Section: Bariatric Surgery and The Immune Systemmentioning
confidence: 99%
“…However, a sometimes-complicated notion is that obesity also leads to compensatory immunosuppressive mechanisms to avoid a constant, full-blown pro-inflammatory response, similar controlling any immune reaction, to maintain homeostasis. These mechanisms include reduced absolute numbers of activated CD8 + T cells, T cell suppression by PD-1 [241,242], T cell exhaustion [243], and dysfunctional NK cells [244]. Thus, obesity induces a complex and dynamic state of pro-inflammatory immune cell content and function with an influx of monocyte-derived "M1"-like macrophages, combined with reductions in immunomodulatory/ regulatory or dysfunctional immune cells such as regulatory T cells (Tregs), "M2"-like macrophages, or NK Cells, together with an induction of checkpoint ligands (discussed below) [245][246][247][248], and elevated immunosuppressive cells such as immature monocytes or myeloid-derived suppressive cells (MDSCs) [249][250][251][252][253].…”
Section: Bariatric Surgery and The Immune Systemmentioning
confidence: 99%
“…These cells are characterized by reduced proliferative capacity and telomerase activity and show adverse metabolic changes. PD-1 blockade has been proposed as a therapeutic intervention, with a potential to enhance T cell priming in obese individuals [78], whereas senolytics (that induce senescent cell death), such as the CD153 vaccine, have been shown to ameliorate senescent T cells accumulation in adipose tissue in animal models [13].…”
Section: Discussionmentioning
confidence: 99%
“…Obesity acts by impairing antigen-specific T-cell priming through PD-1/PD-L1 axis upregulation. Thus, PD-1 blockade in this setting results in both greater responsiveness and greater incidence of adverse reactions [ 117 ]. Interestingly, a real-life, multicenter, retrospective observational study involving more than one thousand patients has indeed revealed that higher body mass index was significantly related to the higher occurrence of any grade irAEs, grade 3 and grade 4 irAEs, and irAEs leading to treatment discontinuation [ 118 ].…”
Section: General Considerations On Predictors and Biomarkers For Immu...mentioning
confidence: 99%